Autologous serum eye drops for patients with dry eye disease: a systematic review and meta-analysis of randomized controlled trials - He, Chang-Zhu; Zeng, Zhao-Jun; Liu, Jun Qiao; Qiu, Qin; He, Yu (Frontiers in Medicine, 2024)
Background: Dry eye disease (DED) is highly prevalent worldwide, leading to increased medical costs, economic burdens on families and society, and a diminished quality of life for patients. The utilization of autologous serum eye drops (ASEDs) for the treatment of DED is progressively rising. Objective: To further evaluate the efficacy and safety of ASEDs in the treatment of DED. Methods: A thorough search for randomized controlled trials (RCTs) was conducted across eight databases, including PubMed, EMBASE, the Cochrane Library, Web of Science, China National Knowledge Infrastructure, Wanfang, SinoMed, and VIP. This search encompassed the inception of each database up to April 1, 2024, with a specific focus on identifying RCTs evaluating the efficacy and safety of ASEDs for the treatment of DED. Data analysis was conducted utilizing Stata 15.0 software and the Cochrane Risk of Bias Assessment Tool was utilized to appraise the literature's quality. Results: The study encompassed twelve RCTs. In comparison to the use of artificial tears (AT), patients diagnosed with DED who utilized ASEDs displayed elevated the Schirmer test (ST) scores [WMD = 2.35, 95% CI (1.45, 3.24), P <0.001] and tear-film breakup time (TBUT) scores [WMD = 2.83, 95% CI (2.27, 3.39), P <0.001], decreased Corneal fluorescence staining (CFS) scores [SMD = -2.11, 95% CI (-3.07, -1.15), P <0.001] and the Ocular Surface Disease Index (OSDI) scores [WMD = -10.54, 95% CI (-13.31, -7.77), P <0.001], and experienced a reduced frequency of adverse events [RR = 0.36, 95% CI (0.13, 0.99), P=0.048]. Conclusions: In this study, ASEDs had been shown to enhance tear secretion, extend tear film break-up time, mitigate corneal epithelial damage, ameliorate OSDI scores, and exhibit greater safety compared to AT.